Peran Tasawuf dalam Meraih Kecerdasan Intelektual, Emosional dan Spiritual di Era Modern - Ananda Julyani Azzahra (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the role of Sufism in achieving intellectual, emotional and spiritual intelligence in the modern era. This study used a qualitative approach using a descriptive-analytical method. The results and discussion in this study show how important the role of Sufism is to be studied in increasing the three intelligences possessed by humans, namely intellectual, emotional and spiritual, especially in today's modern era. Increasing intelligence itself can be done by means of riyadhah, habituation, and mujahadah. This research concludes that Sufism plays a role in achieving intellectual, emotional and spiritual intelligence. This research recommends Islamic educational institutions to develop the cultivation of Sufism values in achieving intellectual, emotional and spiritual intelligence in the modern era.